Perceived threat of crime, authoritarianism, and the rise of a populist president in the Philippines. Issue 3 (3rd July 2019) - Maxwell, Sheila Royo
ABSTRACT: President Duterte of the Philippines implemented an open "war" on drugs based upon claims of an over-proliferation of illegal drugs in the country. Despite summary killings of suspected users and dealers, Duterte enjoys popular support among Filipinos. This paper assesses reasons behind the support using citizens' perceptions of the severity of the drugs/crime problem, their punitiveness, and authoritarian attitudes as explanations. A sample of 114 Filipinos across Luzon, Visayas and Mindanao responded to an electronic survey about socio-legal issues. Results show that drugs/crime are perceived as serious problems nationally yet only minor problems locally . This perceived national seriousness is significantly related to support for Duterte. Trust in the law and enforcement agents, an authoritarian attitude, and region are also strongly related to support for Duterte. This paper concludes with reflections on information manipulation as means to advance political ends and the importance of context in furthering theories of authoritarian submission.